Fantastic Beasts and Where to Find Them : The Original Screenplay - Rowling, J.K (Little, Brown, 2016)
While attending the Magical Congress of the United States of America in 1926, Newt Scamander is pursued by the wizarding authorities when dangerous beasts and their habitats escape from his magical briefcase.